Survival of Glass Ionomer Restorations in Primary Molar Teeth in a Tertiary Hospital in Chitwan - Adhikari, S; Tamrakar, L; Bhattarai, R; Thapa, V (Journal of Nepalese Prosthodontic Society, 2022)
Introduction: Glass ionomer cement (GIC) is frequently used as a restorative material in dentistry and has been known for its anti-carious property, biocompatibility and good marginal adaptation. The study aims to evaluate the survival of GIC restorations on primary molar teeth of dental patients attending College of Medical Sciences, Chitwan. Methods: A retrospective longitudinal study was conducted among the patients who were treated with, at least one GIC restoration (GC Fuji II/GC Fuji IX GP) in their primary molars during the past three years. Data were collected to assess the demographic variables like gender, economic status and mother’s education; restoration-related variables like no of surfaces involved, type of material used, location of the restoration in oral cavity, and age of restoration and; outcome related variable i.e. survival of restoration (survived / failed). United States Public Health Service (USPHS) criteria was used to determine survival. Data analysis was done using software SPSS version 17. Chi-square tests were carried out to find out the association between dependent and independent variables. Significance level was set at p<0.05. Results: The 1-3 years cumulative survival rate of the GIC restoration in primary molars was found to be 74.5%. The survival rates for 1 year, 2 years and 3 years were found to be 93.5%, 78.6% and 62.5% respectively. There was no significant association between the survival of the restoration and location of the tooth in oral cavity and sociodemographic indicators like gender, age, economic status and mother’s education. However, statistically significant association was found between survival of restoration and type of restorative material, number of surfaces involved and age of restoration. Type VIII GIC had a higher survival rate (85.7%) compared to Type II GIC (68.2%), and single-surface restorations had a higher survival rate (84.9%) compared to two-surface restorations (52.3%). Conclusion: Our findings suggest that GIC can be used for restoring primary molars, particularly as single-surface restorative material. It also suggests that Type VIII GIC can more effective in restoring the primary molars as compared to the conventional Type II GIC.